2020
DOI: 10.1007/s12055-020-00924-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast tracking after repair of congenital heart defects

Abstract: Fast tracking after repair of congenital heart defects (CHD) is a process involving the reduction of perioperative period by timely admission, early extubation after surgery, short intensive care unit (ICU) stay, early mobilisation, and faster hospital discharge. It requires a coordinated multidisciplinary team involvement. In the last 2 decades, many centres have adopted the fast tracking strategy in paediatric cardiac population, safely and successfully extubating patients in the OR with reported benefits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We are unaware of other contemporary multicenter assessments that could confirm our finding that EE rates have not increased over the past decade regardless of age, surgical complexity, or center volume, but the consistency of this observation among all subgroups we evaluated supports its validity. This is despite many single-center and multicenter reports showing that EE is feasible in most postoperative cardiac patients, even in younger children with complex cardiac lesions (28–32), and a recent consensus statement from the American Association for Thoracic Surgery stating that EE is an “integral component” to enhance postoperative recovery in children (19).…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of other contemporary multicenter assessments that could confirm our finding that EE rates have not increased over the past decade regardless of age, surgical complexity, or center volume, but the consistency of this observation among all subgroups we evaluated supports its validity. This is despite many single-center and multicenter reports showing that EE is feasible in most postoperative cardiac patients, even in younger children with complex cardiac lesions (28–32), and a recent consensus statement from the American Association for Thoracic Surgery stating that EE is an “integral component” to enhance postoperative recovery in children (19).…”
Section: Discussionmentioning
confidence: 99%
“…9 One approach to this problem is to control the stress response with regional anesthesia while lowering the dose of intravenous narcotics. Garg et al 3 reported on a series of 1000 patients in which 40% of the neonates and 81% of the infants undergoing a variety of complex cardiac operations, including the Norwood procedure, were able to be extubated in the operating room. This was accomplished by limiting intravenous fentanyl to 5 µg/kg and using a single-shot caudal injection of morphine and DEX.…”
mentioning
confidence: 99%
“…This was accomplished by limiting intravenous fentanyl to 5 µg/kg and using a single-shot caudal injection of morphine and DEX. 3 Likewise, Xu et al 6 used a reduced dose of sufentanil supplemented with ropivacaine peripheral nerve blocks to facilitate extubation in the operating room after cardiac surgery in infants, with an average extubation time of 22 min. 6 Maharramova performed a meta-analysis of the use of caudal anesthesia in congenital heart surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations